Hyperkeratotic warty skin lesion of foot caused by Fusarium oxysporum - Ravinder Kaur; Megha Maheshwari (Wolters Kluwer Medknow Publications, 2013)
Fusarium species are common soil-inhabiting organisms and plant pathogens. Human infections are usually precipitated by local or systemic predisposing factors, and disseminated infection is associated with impaired immune responses. Skin infections caused by Fusarium spp. include keratitis, onychomycosis, mycetoma, painful discrete erythematous nodules. Hyperkeratotic skin lesions caused by Fusarium spp. are, however, rarely reported. We report a case of hyperkeratotic verrucous warty skin lesion in the foot of a 50-year-old immunocompetent male, farmer by occupation.